2019
DOI: 10.3389/fonc.2019.00859
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Multicenter Long-Term Follow-up Analysis of Prognostic Risk Factors for Recurrence-Free, Metastasis-Free, Cancer-Specific, and Overall Survival After Curative Nephrectomy in Non-metastatic Renal Cell Carcinoma

Abstract: We evaluated prognostic risk factors of recurrence-free survival (RFS), metastasis-free survival (MFS), cancer-specific survival (CSS), and overall survival (OS) outcomes in patients with non-metastatic renal cell carcinoma (nmRCC) after curative nephrectomy during long-term follow-up. The medical records of 4,260 patients with nmRCC who underwent curative nephrectomy between 2000 and 2012 from five Korean institutions and follow-up after postoperative 1 month until December 2017 were retrospectively analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Previously, anaemia has been suggested as a prognostic factor in RCC. Kim et al retrospectively analysed data of 4260 patients that had non-metastatic RCC and found anaemia was highly associated with worse recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) [ 17 ]. Jiwei Huang et al analysed the data of 352 papillary RCC patients and found that patients with preoperative anaemia had significantly worse RFS, CSS, and OS than those without it (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, anaemia has been suggested as a prognostic factor in RCC. Kim et al retrospectively analysed data of 4260 patients that had non-metastatic RCC and found anaemia was highly associated with worse recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) [ 17 ]. Jiwei Huang et al analysed the data of 352 papillary RCC patients and found that patients with preoperative anaemia had significantly worse RFS, CSS, and OS than those without it (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, anemia could be used as a prognostic factors in RCC. Kim SH et al retrospectively analyzed 4,260 patients with non-metastatic RCC and found factors include anemia were associated with worse recurrence-free survival (RFS), cancer-speci c survival (CSS), and overall survival (OS) [16]. Jiwei Huang et al analyzed 352 patients with papillary RCC and found patients with preoperative anemia had signi cantly worse RFS, CSS, and OS than patients without anemia (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the patients with clear cell renal cell carcinoma (ccRCC) develop metastases [1]. Even after surgical treatment of early non-metastatic kidney cancer, metastases occur in 5-15% of cases within five years of follow-up, which significantly affect the survival of patients [2]. The frequency of metastasis can be about three-fourths of all relapse cases and is weakly associated with some clinical characteristics [3].…”
Section: Introductionmentioning
confidence: 99%